(untitled) - HARDIYANTI, INDRA (LATERNE, 2013)
Writing skills is a very complex language skills that must be mastered students, because the writing students must master some language elements such as vocabulary and grammar. But in reality the students are still having difficulties in writing skills, for that teachers need to apply new methods in learning activities so that students can more easily absorb the material being taught. One stu method suitable for use in writing skill is game. The gamemethod is charades game. Because in charades game students must apply the language elements such as vocabulary and continuously. So the game of charades is considered good in improving writing skills .The formulation of this study were (1) how to raise the game of charades in the writing skills of students in class XI IPA 5 SMAN 14 Surabaya? (2) how the learning outcomes of students of class XI IPA 5 of the application perminancharades in improving writing skills.The purpose of this study was to describe the application of charades game writing skills in the process of learning German in students class XI IPA 5 SMAN 14 Surabaya and the resulting increase student learning in class XI IPA 5 SMAN 14 Surabaya in writing skills using the game of charades .This study used a qualitative descriptive method. Existing data are observational data obtained by the students in learning activities in the classroom and the data from the test scores at each meeting. The data is analyzed based on the theory that has been collected in the literature review chapter. The results of these studies indicate that an increase in the percentage of student learning outcomes and increasing student activity so that it can be said charades learning model can be used in improving writing skills. Keywords: games, charades, writing skills, activities of student learning outcomes